The effect of lime juice as cavity cleanser on the tensile strength of self-etch adhesive system - Widyastuti, Noor Hafida; Rini, Desnia Sinta (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Composite resin restorative materials cannot bond directly with the tooth structure, so an adhesive material is necessary. The strength of the adhesive bond is affected by the presence of a smear layer which can be cleaned using a cavity cleanser. The purpose of this study was to determine the effect of lime juice (Citrus aurantifolia S.) as a cavity cleanser on the tensile strength of generation VIII self-etch adhesive materials. Methods: The research that has been conducted is a true experimental laboratory study using a post test only control group design. The research was carried out using the Universal Testing Machine to measure the amount of force required to release the adhesion between the two materials. The treatment group consisted of 3 groups: group I was not given any ingredients (negative control), group II was given chlorhexidine (positive control), and group III was given lime juice as a cavity cleanser after the cavity preparation procedure. Then the self-etch adhesive material and GV Black class V composite resin filling were applied and a tensile strength test was carried out. The results of the data were then analyzed using the One Way Anova test. Results: The results of the study based on the One Way ANOVA test and the LSD post-hoc test showed a value of p = 0.00 (p <0.05), which means that there were differences between the three study groups. This is because lime juice contains saponins and citric acid which can clean the smear layer. Conclusion: lime juice (Citrus aurantifolia S.) has the effect of increasing the tensile strength of self-etch adhesive materials.KEY WORDS: self-etch adhesive, tensile strength, cavity cleanserPengaruh air perasan jeruk nipis (Citrus aurantifolia S.) sebagai cavity cleanser terhadap kekuatan tarik bahan adhesive self-etchABSTRAKPendahuluan: Bahan restorasi resin komposit tidak dapat berikatan langsung dengan struktur gigi sehingga diperlukan suatu bahan adhesif. Kekuatan ikatan adhesif dipengaruhi oleh keberadaan smear layer yang dapat dibersihkan menggunakan cavity cleanser. Tujuan penelitian ini adalah mengetahui adanya pengaruh air perasan jeruk nipis (Citrus aurantifolia S.) sebagai cavity cleanser terhadap kekuatan tarik bahan adhesif self etch generasi VIII. Metode: Penelitian yang telah dilakukan merupakan penelitian true eksperimental laboratorium menggunakan posttest only control group design. Penelitian dilakukan dengan menggunakan alat Universal Testing Machine mengukur besarnya gaya yang dibutuhkan untuk melepaskan pelekatan antara dua bahan. Kelompok perlakuan terdiri dari 3 kelompok yaitu kelompok I tidak diberikan bahan apapun (kontrol negatif), Kelompok II diberikan chlorhexidine (kontrol positif), dan kelompok III diberikan air perasan jeruk nipis sebagai cavity cleanser setelah prosedur preparasi kavitas. Selanjutnya diaplikasikan bahan adhesif selfetch dan tumpatan resin komposit GV Black kelas V dan dilakukan uji kekuatan tarik. Hasil data kemudian dianalisis menggunakan uji One Way Anova. Hasil: hasil penelitian berdasarkan uji Oneway ANOVA dan post-hoc test LSD menunjukkan nilai p=0,00 (p<0,05) yang berarti terdapat perbedaan diantara ketiga kelompok penelitian. Hal ini disebabkan karena air perasan jeruk nipis mempunyai kandungan saponin dan asam sitrat yang dapat membesihkan smear layer. Simpulan: Air perasan jeruk nipis (Citrus aurantifolia S.) memiliki pengaruh meningkatkan kekuatan tarik bahan adhesif self etch.KATA KUNCI: adhesif self-etch, kekuatan Tarik, cavity cleanser